Quantitative evaluation of tight oil reservoirs in the Chang 8 Member of the Yanchang Formation in southern Ordos Basin - Luan, Beibei; Zhang, Bo; Wang, Didong; Deng, Chao; Wang, Feng (Frontiers in Earth Science, 2022)
The precise and quantitative characterization of reservoir properties is the key to efficient development of tight oil reservoirs. In this paper, taking the Chang 8 Member of the Yanchang Formation in the Shuimogou area in the southern Ordos Basin as an example, the sedimentary facies type, microscopic pore structure, diagenesis, influencing factors of physical properties, and hydrocarbon enrichment law of tight oil reservoirs in the Chang 8 Member are systematically studied. The research results show that the Chang 8 Member in the study area is a typical delta front subfacies deposit, including distributary channel and inter-distributary bay microfacies. The constructive diagenesis of the Chang 8 Member includes dissolution, metasomatism and rupture; while the destructive diagenesis includes mechanical compaction and cementation. The Chang 8 reservoir has entered the middle diagenetic stage A. The factors affecting the physical properties of tight oil reservoirs include deposition, compaction, cementation and dissolution. The secondary pores formed by dissolution account for 10%-40% of the total surface porosity, with an average of 24%. Local structures and sediments have significant control over hydrocarbon accumulation. The westward dipping tectonic setting of the northern Shaanxi Slope provides the basic conditions for the migration of oil and gas to the eastern updip direction. The changes of lithology and physical properties in the updip direction of the structure form the blocking conditions for the continued migration of oil and gas, which is conducive to the accumulation of oil and gas. In addition, the main oil reservoirs are mainly distributed along the distributary channel of the delta front, and most of the distributary channel sandstone is more than 20 m thick. The distribution area of thick sand body with multiple layers in the lateral direction is the main part of oil and gas accumulation. However, the reservoirs formed on the flanks of underwater distributary channels are thin and poorly sorted, which is not conducive to the accumulation of hydrocarbons.